Nalidixic acid—a good marker of fluoroquinolone resistance mechanisms in Escherichia coli - Sofia Kalinen; Heini Kallio; Teemu Kallonen; Juha Knaapila; Tarja Lamminen; Pentti Huovinen; Peter Boström; Antti J. Hakanen; Marianne Gunell (Microbiology Spectrum)
ABSTRACT The purpose of this study was to evaluate how ciprofloxacin, pefloxacin, and nalidixic acid disks perform in screening fluoroquinolone resistance mechanisms in 278 Escherichia coli isolates collected from a prospective clinical material. Antimicrobial susceptibility testing of ciprofloxacin, pefloxacin, and nalidixic acid was performed with the disk diffusion method. PCR-based and sequencing methods were used to detect chromosomal mutations in the gyrA and parC genes and the presence of plasmid-mediated qnr and aac(6′)-1b-cr genes. In addition, whole-genome sequencing was used to confirm these results. Our results show that fluoroquinolone resistance mechanisms were discovered, even in ciprofloxacin-susceptible isolates, and plasmid-mediated low-level fluoroquinolone resistance is easily missed if only ciprofloxacin disk is used. E. coli strains with chromosomal gyrA and/or parC mutations were well detected with pefloxacin disk. However, nalidixic acid was a superior tool to detect and differentiate between low- (plasmid-mediated) and high-level (chromosomal mutations) fluoroquinolone resistance in E. coli. Thus, more clinical studies are needed to evaluate the clinical relevance of fluoroquinolone resistance mechanisms in enteric bacteria and pathogens that show potential but are not yet phenotypically fluoroquinolone-resistant.IMPORTANCEWe show in our clinical setting that fluoroquinolone resistance mechanisms are discovered, even among phenotypically fluoroquinolone-susceptible Escherichia coli isolates. When plasmid-mediated quinolone-resistance determinants are present, they are a potential risk for treatment failures due to accumulation of resistance mechanisms during the antimicrobial treatment. Therefore, when it is clinically relevant, fluoroquinolone resistance mechanisms in E. coli should be monitored more closely, and we also recommend testing nalidixic acid susceptibility.